NEUROPSYCHOLOGICAL ASSESSMENT TO ADULT POPULATION; ASSESSMENT INSTRUMENTS - Esperanza Bausela Herreras (CAEN, 2008)
In this paper we study the assessment neuropsychological in compressive context. We study the instruments which have been very often applied, one of them are not instruments neuropsychology, also these are applied in this context, the aim is known which is the neurology subtract which is underneath; others have been traditionally neuropsychological instruments, we are going to deep in one of them, the batteryLuria-DNA. We are going to deep in neuropsychological batterys.